The Moral Values and Personalities of the Characters in the Film Budi Pekerti Directed by Wregas Bhanuteja - Thalia Margareta; Siti Rukiyah; Darwin Effendi (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to describe the forms of moral values and to analyze the character personalities portrayed in Wregas Bhanuteja’s film Budi Pekerti (2023) through the lens of Sigmund Freud’s psychoanalytic theory. Employing a descriptive qualitative method, data were collected through documentation, observation, and note-taking. Data validity was ensured via triangulation, and analysis focused on identifying moral constructs and Freudian personality structures. The analysis identified five forms of moral values concerning relationships with oneself, others, society, nature, and God. Furthermore, 31 instances of Freudian personality structures were quantified: the Id (10 instances), the Ego (25 instances), and the Superego (6 instances), revealing the dynamic internal conflicts driving the characters. This research offers a novel psychoanalytic excavation of a contemporary Indonesian film, applying Freud’s tripartite model to quantify and interpret the manifestation of personality structures within a modern cinematic narrative. The study provides a framework for educators and media analysts to systematically deconstruct moral messaging and psychological depth in films, using them as tools for character education and media literacy. It contributes to the field of cultural studies by demonstrating the applicability of classical psychological theory to modern media, enriching the understanding of character construction and moral discourse in Indonesian cinema.